2003
DOI: 10.5012/bkcs.2003.24.8.1061
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of the Intramolecular Water Vibrations and Hydrogen Bond in N-Methylacetamide-Water Complexes: Ab Initio Calculation Studies

Abstract: The correlation between the water and N-methylacetamide (NMA) intramolecular vibrational frequencies and the hydrogen-bond length in a variety of NMA-H 2 O and NMA-D 2 O complexes was investigated by carrying out ab initio calculations. As the hydrogen-bond length decreases, the frequencies of bending and stretching modes of the hydrogen-bonding water increases and decreases, respectively, and the amide I and II (III) mode frequencies of the NMA decreases and increases, respectively. In this paper, correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…To check the validity of this approach, we calculated δω CO and δω NH as a function of r OH at a fixed angle of ∠CO···H = 120° (Figure a). In this calculation, the frequency of the isolated amide I mode was set to 1707 cm -1 for a direct comparison to recent ab initio calculations of NMA−water clusters and the NMA dimer. , By adjusting κ CO to 0.42 and κ NH to 0.96 cm kJ mol -1 , the distance dependence of the direct and indirect hydrogen-bond shifts agree quite well with those from the calculations. , The coefficient 0.42 for κ CO is also a reasonable value compared with 0.38 reported for N , N -dimethylacetamide 80 and 0.51−2.2 reported for other carbonyl modes. , For the frequency shift due to solvent exposure, we considered that δω solvent = 0 for the inner residues that are forming two hydrogen bonds to other residues. These residues are relatively shielded from solvent because of the protection provided by bulky side chains of Aib and (αMe)Val residues.…”
Section: Theoretical Calculationssupporting
confidence: 60%
See 1 more Smart Citation
“…To check the validity of this approach, we calculated δω CO and δω NH as a function of r OH at a fixed angle of ∠CO···H = 120° (Figure a). In this calculation, the frequency of the isolated amide I mode was set to 1707 cm -1 for a direct comparison to recent ab initio calculations of NMA−water clusters and the NMA dimer. , By adjusting κ CO to 0.42 and κ NH to 0.96 cm kJ mol -1 , the distance dependence of the direct and indirect hydrogen-bond shifts agree quite well with those from the calculations. , The coefficient 0.42 for κ CO is also a reasonable value compared with 0.38 reported for N , N -dimethylacetamide 80 and 0.51−2.2 reported for other carbonyl modes. , For the frequency shift due to solvent exposure, we considered that δω solvent = 0 for the inner residues that are forming two hydrogen bonds to other residues. These residues are relatively shielded from solvent because of the protection provided by bulky side chains of Aib and (αMe)Val residues.…”
Section: Theoretical Calculationssupporting
confidence: 60%
“…First, hydrogen-bond strength depends on both distance and angle (there is an angle criterion for hydrogen-bond formation), but this formula does not consider angle dependence. Second, it has been experimentally and theoretically shown that hydrogen bonding on the CO and N−H group of the NMA molecule shifts the amide I frequency by approximately 15−25 and 10−15 cm -1 , respectively, and the frequency shifts are additive. Thus, it is necessary to modify the formula to account for the frequency shift due to the N−H group being hydrogen-bonded. Another potential approach to estimate the amide I local mode frequencies is to utilize the linear relationship between the CO bond length and the amide I local mode frequency obtained in recent theoretical studies. , This approach requires an accuracy of at least 10 -3 Å for the calculated bond lengths.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The frequency shifts were found to be in good correlation with the electrostatic energy of the intramolecularly hydrogen-bonded CO•••H−N groups, denoted as E KS . 279 By matching the model frequency shift to the results obtained from quantum mechanical calculations of NMA−water clusters, 334 the correlation coefficients in the above equations were obtained. 78,278 In addition to the intramolecular H-bonding effects, if the CO or N−H group is exposed to solvent, it is necessary to consider an additional decrease (increase) of the amide I (II) mode frequency due to the effect of solvation (δω solvent ).…”
Section: Amide II and Iii Vibrationsmentioning
confidence: 99%
“…Nonlinear-IR spectroscopy of the amide I band can be modeled to obtain C ( t ) and other dynamical quantities. As NMA involves a single amide group, there has been considerable interest in measuring the frequency response of the amide I band of NMA and other peptides in various solvent environments. ,, …”
Section: Introductionmentioning
confidence: 99%